QUATERNARY LANDSLIDES OF THE SOUTHERN COAST OF CRIMEA GEOLOGICAL FORMATION CONDITIONS - Бойко, K. Є. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2016)
The number of landslides within the Southern Coast of Crimea is constantly growing. However, the analysis of previous studies indicates that the landslide formation process mainly depends not so much on the impact of anthropogenic factors but on the influence of nature controlled conditions characteristic of the mountainous region. These conditions include geological-lithological, geological-morphological, climatic and hydrogeological. Thus, the analysis of quaternary structural forms and their display in the relief, as well as of the relief evolution resulting from endogenous and exogenous processes should serve as a basis for correct prediction of contemporary landslide activation and landslide-hazard area modeling. The aim of the article is to analyze and identify major regularities of the relief and the geological structure as the cover landslide development environment and substantiate the use of certain geomorphological and geological criteria for the purpose of classification of the study area according to the landslide hazard degree. In the course of the study we used the key provisions of H.S. Zolotariov’s historical-geological analysis and V.P. Filosofov’s morphometric analysis. As a result, spatial and depth limits of shallow landslide development have been outlined. In addition, the area has been divided into sites according to the potential stability of the geological environment. The obtained results will be further used to build a mapping model and conduct quantitative prediction of landslide-hazard areas of the Southern Slope of the Crimean Mountains.